Inventarisasi Kejadian Penyakit pada Ternak Kambing Bantuan Pemerintah di Desa Petaling Jaya, Kecamatan Kumpeh Ulu, Kabupaten Muaro Jambi Propinsi Jambi - Rahayu, Pudji (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2008)
The  survey  research  was  conducted  to  investigate  disease  grouping  which  spred  among governmental  grat  goat  in  desa  Petaling  Jaya.  Thirty  six  farmers  which  owned  304  heads  were  used  as respondent. Data collected were disease groups according to spreading into goat and diseases which were found  during  research  time.  The  result  indicated  that  al  of  the  farmers  (100%)  reported  that  their  goat had  spred  by  scabies,  100  %  worm,  milk  production  problem  (100%),  16  respondents  (44.4%)  feed consuption  problem  and  5  respondents  (14%)  swollen  disease.  However,  there  were  only  4  kinds  of diseases  which  caused  goat  death  such  as  scabies,  milk  production  problem,  feed  consumption  problem and swollen disease. From the result we concluded that there were 4 kinds of diseases which were spred into goat in that region such as scabies, worm, milk production problem and feed consumption problem.